Effects of Physical Activity and Dietary Intervention on Metabolic Risk Factors Among Employees of Universiti Putra Malaysia. - Heng, Kiang Soon (2011)
In Malaysia, the prevalence of obesity has now reached an alarming level. However, to date there is still a lack of published controlled study of the physical activity and dietary intervention on metabolic risk factors in Malaysian adults. A twelve-week quasi-experimental community-based intervention study was carried out to evaluate the effects of physical activity and dietary intervention on metabolic risk factors among the employees of Universiti Putra Malaysia (UPM), Serdang, Selangor Darul Ehsan. The faculties and other institutes in UPM were grouped into four clusters which were then randomly assigned for the recruitment of participants into the following four groups: physical activity (PA) group, diet group, physical activity plus diet group (PA+diet) and control group. Participants consisted of adults aged 25 to 55 years with abdominal obesity and no reported chronic diseases. The PA group received PA intervention which promotes increasing walking steps. The diet group received dietary intervention aiming at reducing caloric intake. The PA plus diet group received both PA and dietary intervention. At baseline, 134 persons participated in the intervention program. Upon completion of the program, the final sample consisted of 112 participants, with an equal number of 28 for each study group. There was no significant increase in total daily energy expenditure and daily steps in PA and PA plus diet group. Besides, no significant reduction in calorie intake was observed in diet and PA plus diet group. For weight, percentage of body fat, body mass index (BMI), waist circumference (WC) and waist-hip ratio (WHR), ANCOVA and repeated measures ANOVA analysis showed that there was neither significant difference in magnitude of changes in intervention groups as compared to control group nor among intervention groups themselves. For hip circumference, a significantly greater improvement in hip circumference was observed for PA plus diet group compared to control group. Looking at within group effects, there was a significant increase in BMI (p=0.035), percentage of body fat (p=0.010) and hip circumference (p=0.019) between baseline and twelfth weeks in PA group. In the same group, a significant reduction in WHR was found. In PA plus diet group, a significant increase in hip circumference was detected (p=0.002). A significant group effect was observed for LDL cholesterol and fasting plasma glucose. For LDL cholesterol, ANCOVA with Bonferroni adjustment indicated that PA plus diet group had a significantly greater decrease (p=0.018) than control group. For fasting glucose level, Repeated Measures ANOVA showed a significantly greater reduction (p=0.042) in PA plus diet group compared to PA group. However, no “time x group” effect was detected. Within group, there was significant a decrease in triglycerides (p=0.006), total cholesterol (p=0.0001) and LDL cholesterol (p=0.0001) in diet group. A significant decrease in diastolic blood pressure (p=0.0001) and a significant increase in HDL cholesterol (p=0.029) was observed in PA group. For PA plus diet group, a significant reduction was found for triglycerides (p=0.0001), total cholesterol (p=0.0001), LDL cholesterol and fasting plasma glucose (p=0.005). Conversely, a significant increase in diastolic blood pressure was observed in control group (p=0.044). As conclusion, PA or dietary intervention alone was not effective in improving the obesity and metabolic parameters. Only combined PA and diet intervention was effective in improving some of the obesity and metabolic parameters among participants with abdominal obesity. However, overall PA plus diet intervention was not superior to either PA or diet intervention alone except in reducing fasting plasma glucose level. The findings from the study are useful to further improve group-based intervention for the prevention and management of obesity.